Pengaruh Adversity Quotient (AQ) terhadap Kinerja Guru dengan Motivasi Kerja sebagai Variabel Mediasi pada Guru SMK PGRI Wonoasri Kab Madiun - Novi Meiyrdhayanti (JRMA (Jurnal Riset Manajemen dan Akuntansi), 2017)
This study aimed to examine the effect of direct and indirect adversity quotient on teacher performance SMK PGRI Madiun Wonoasri through motivation to work as a variable pemediasi. Samples from this study are all teachers of SMK PGRI Madiun Wonoasri. Instrument data collection using questionnaires. Data were analyzed using regression analysis and path analysis. The analysis showed that the adversity quotient significant positive effect on work motivation, adversity quotient significant positive effect on Kinerrja, and motivation significant positive effect on the performance of teachers. Work motivation has partial mediation role in the influence of adversity quotient on teacher performance.